If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (5x + -3) = 7 Reorder the terms: 3x + (-3 + 5x) = 7 Remove parenthesis around (-3 + 5x) 3x + -3 + 5x = 7 Reorder the terms: -3 + 3x + 5x = 7 Combine like terms: 3x + 5x = 8x -3 + 8x = 7 Solving -3 + 8x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = 7 + 3 8x = 7 + 3 Combine like terms: 7 + 3 = 10 8x = 10 Divide each side by '8'. x = 1.25 Simplifying x = 1.25
| 3(2x-5)+6(x+2)= | | 5x+3=x+31 | | 3+.5x=17-3x | | lx+6l=9 | | -4=w-30 | | 10+2x=15+1x | | 8y-3=6y+7 | | 96+12x+30=180 | | x*5-2x=38 | | a+5a=2a+9 | | A=.05bcd+bc | | 4+5x=x+23 | | t+28=13 | | a+5a=2a+a | | -6-3=3x+6-6 | | 1y-2=.33(y+6) | | 9=9-8h | | 5x-1y=15 | | 48+4y-18=14y-12-4y | | X+24=32X | | 3a^2+9a+12=0 | | 4k+8-6k= | | x+x=6+2 | | r(r+3)=0 | | 2y=82 | | 3a^2+9a-12=0 | | 1963-5x=1863 | | n+6/21=4/7 | | 3x+1(-2x+9)=7 | | 36-2(6-2x)=-16 | | n+15=3l | | n/11=40/55 |